Fertilización de npk y la influencia en las características agronómicas del pepino (Cucumis sativus L.) en el distrito de Yurimaguas, 2020 - Saldaña Martinez, Sandra Lucia (2021)
The Present Thesis Work was developed in the University field of the Faculty of Zootechnics of the National University of the Peruvian Amazon, Located on the Yurimaguas - Tarapoto Highway, km 18 in the Alto Amazonas Province, Loreto Region, city of Yurimaguas, with the purpose of determining the NPK fertilization and the influence on the agronomic characteristics of Cucumber (Cucumis sativus L.). The evaluated indicators were: plant height (cm), fruit diameter (cm), fruit length (cm), number of fruits / plant, fruit weight (gr) and yield (kg / ha); A Random Complete Blocks (D.B.C.A) design with five treatments and four repetitions was used. The treatments were: T1 (control), T2 (100 kg of NPK / ha), T3 (120 kg of NPK / ha), T4 (140 kg of NPK / ha) and T5 (160 kg of NPK / ha). In the thesis work, the following results were obtained: Regarding the height of the plant (cm), values of 101.8 cm, 84.81 cm, 117.88 cm, 126.94 cm and 135 cm were reported, respectively. Regarding the diameter of the fruits (cm), it was reported: 5,495 cm, 5,645 cm, 5,815 cm, 5.79 cm and 6 cm, respectively, with no significant statistical differences between treatments (P> 0.05). Regarding the length of the fruits, values were obtained: 15.78 cm, 17.51 cm, 18.26 cm, 18.74 cm and 20.54 cm, respectively, with a significant difference between the treatments (P <0.05). Regarding the number of fruits/plant, it was obtained: 3.3; 3.6; 3.2; 3.6 and 4.2, respectively, with no statistically significant differences between treatments (P> 0.05). Regarding the weight of fruits (gr), the following were obtained: 189.375 gr, 264.7 gr, 264.75 gr, 323.75 gr and 422.2 gr, respectively, with a significant difference between the treatments (P <0.05). Finally, regarding the yield, values were obtained: 8071 kg / ha, 10744.5 kg / ha, 11515 kg / ha, 13040.5 kg / ha and 17142.5 kg / ha respectively, with a significant difference between the treatments (P <0.05).